KARAKTERISASI MIRISTISIN HASIL ISOLASI MINYAK PALA - Souhoka, Fensia Analda; Sohilait, Hanoch J; Fransina, Eirene G (Prodi Pendidikan Kimia FKIP Universitas Pattimura, 2018)
Characterization of Myristicin isolated from nutmeg oil has been done. The study was started by isolating the nutmeg oil from the nutmeg using steam distillation for 8 hours, yield 2.40% of nutmeg oil. The isolation of myristicin from nutmeg oil by fractional distillation under reduced pressure, yield 8.02% of myristicin with 100% of purity. The purity was determinated using GC and the structure elucidation was analyzed by FTIR, 1H-NMR, and MS spectromecters